2018
DOI: 10.1002/adma.201803550
|View full text |Cite
|
Sign up to set email alerts
|

3D Microstructured Scaffolds to Support Photoreceptor Polarization and Maturation

Abstract: Blinding disorders of the outer retina involve dysfunction and degeneration of photoreceptors. One potential approach to treat these forms of blindness is to repopulate the outer retina via a simple bolus injection of donor photoreceptors. However, this may not be ideal due to the highly polarized organization of photoreceptors that include apical light sensing photopigments and basal axon terminals. Furthermore, bolus injections create uncertainty with regard to the area, density, and retention of donor cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 42 publications
0
46
0
1
Order By: Relevance
“…For example, microfabricated elastomers (nondegradable and degradable) can help organize and polarize photoreceptor precursor cells to form a uniform layer. 10 Further, our group has demonstrated that two-photon polymerization (TPP), a form of high-resolution 3D printing, can also be used to create scaffolds (nondegradable) that organize retinal progenitor cells in a pattern that recapitulates the photoreceptor cell layer. 11 Recently, we also applied this fabrication technique to poly(caprolactone), a degradable polyester, and showed that the resulting scaffolds are well tolerated by retinal cells and in vivo retinal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…For example, microfabricated elastomers (nondegradable and degradable) can help organize and polarize photoreceptor precursor cells to form a uniform layer. 10 Further, our group has demonstrated that two-photon polymerization (TPP), a form of high-resolution 3D printing, can also be used to create scaffolds (nondegradable) that organize retinal progenitor cells in a pattern that recapitulates the photoreceptor cell layer. 11 Recently, we also applied this fabrication technique to poly(caprolactone), a degradable polyester, and showed that the resulting scaffolds are well tolerated by retinal cells and in vivo retinal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…A novel microscaffold enabling to package transplantable photoreceptors has been recently reported. The "wine glass" scaffold designed by Jung and collaborators promoted organization and polarization of human PSC-derived photoreceptors (Jung et al, 2018) that is well-suited for cell replacement therapy. Bioprinting should allow to precisely control the distribution of cells on scaffolds and to obtain multi-layered structures combining RPE and photoreceptors, as recently demonstrated using both RPE and retinoblastoma cell lines (Shi et al, 2018).…”
Section: Futures Directions and Conclusionmentioning
confidence: 99%
“…Whereas many eye diseases can be treated with such surgeries or drug deliveries, some blinding disorders that involve dysfunction or degeneration of the retina must utilize visual prosthesis to restore vision. Especially, no medicinal cures are available for degenerated photoreceptors, the light‐sensitive neurons of the retina 176–178. A team of researchers has developed a visual prosthesis microchip that replaced such degenerated photoreceptors with light sensitive electronic photodetectors, combined with integrated processors and electrodes to complete their interface with the ganglion cells, which receive and send visual information to the brain 42,179.…”
Section: Injectable Systems For the Eye And Earmentioning
confidence: 99%